Wybrane aspekty ustrojowe samorządu terytorialnego na Ukrainie i w Polsce - Owsiak, Wiktor; Prokopiv, Olha (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
This paper presents the significance of the issues related to the activity of territorial self-government for the social and economic development of Ukraine. The efficient operation of self-government in any country is unfeasible without financial resources. Polish experience in the development of territorial self-government is particularly valuable in relation to the reform of Ukraine’s self-government. The paper outlines the differences in the structure and operation of territorial self-government in both countries. The paper is concluded with numerous observations on the direction of selected reforms of Ukrainian self-government. It shows the weaknesses of local self-government in Ukraine, which result from the lack of decentralization of finance and the small amount of state-collected taxes. The conclusions end with the observation that a consistent development of the Ukrainian state is required for Poland to develop well.